Geo-Dynamics, Salinity Gradient, and Vegetation Interdependence in Chilika Lagoon, a Tropical Wetland in Eastern India - Sujit Kumar Mishra; Siba Prasad Mishra; Kalpataru Das (Center for Journal Management and Publication, 2019)
Chilika a shallow brackish lagoon, India, is shrinking for sediment surplus budget. South Mahanadi deltaic branches i.e. Daya and Bhargavi terminate at the southwest swamps of the Lagoon. The annual average salinity of the lake was depleted from 22.31ppt (1957-58) to 8.5 ppt. (1999-2000) as the mixing process of saline and fresh water was influenced from 1995. Trepidation of conversion ofÂ Chilika to a atrophied fresh water lake due to blooming population and their hydrologic interventions like Kolleru lake in (India), Aral Lake (Uzbekistan) was apprehended by 1950â€™s and was alarming by 1999 when the shallow inlet(s) shifted extreme north. The shallow mud flats of lean salinity were reclaimed further for agriculture. The ecology and biodiversity degraded with substantial pecuniary loss to the lagoon dependents. Anthropogenic interventions like, Hirakud dam (1956), dredging of Sipakuda Inlet (2000), Naraj barrage at delta head (2004), Gobardhanpur barrages (1998) and Gabkund cut with weir (2014) were made to the hydraulic system. The deteriorating health, perturbed biodiversity and declined ecosystem of the lagoon has forced to have a comparative study of the various morphologic changes passed over the Chilika with time. The meteorological, hydrologic and the salinity study of the lagoon area for the period 1990 to 2016 have shown changes. Topographic study using GIS is developed by collecting data from Glovis Classic (Google) and the interpretation is done using ERDAS 9.2 software for various geomorphic features (1984 and 2017) before and after the current anthropogenic interventions and compared with previous studies.